The new handbook of research on music teaching and learning : a project of the Music Educators National Conference - Colwell, Richard; Richardson, Carol P; Oxford University Press; Music Educators National Conference (U.S.) (Oxford ; New York : Oxford University Press, 2002)
This handbook features chapters by the world's foremost scholars in music education and cognition. It includes sections on arts advocacy, music and medicine, teacher education, and studio instruction, among other subjects. This new companion volume to the original Handbook of research on music teaching and learning explores the significant changes in music and arts education that have taken place in the last decade. Notably, several chapters now incorporate insights from other fields to shed light on multi-cultural music education, gender issues in music education, and non-musical outcomes of music education. Other chapters offer practical information on maintaining musicians' health, training music teachers, and evaluating music education programs. Philosophical issues, such as musical cognition, the philosophy of research theory, curriculum, and educating musically, are also explored in relationship to policy issues. In addition to surveying the literature, each chapter considers the significance of the research and provides suggestions for future study
Policy frameworks, research, and K-12 schooling / Samuel Hope -- MENC : a case in point / John J. Mahlmann -- Recent trends and issues in policy making / Ralph A. Smith -- Law research and music education / John W. Richmond -- Philosophical perspectives in curriculum / Estelle R. Jorgensen -- Educating musically / Wayne Bowman -- Philosophical perspectives on research / David J. Elliott -- Toward an understanding of the aims of music education / Ian Westbury -- Contemporary curriculum practices and their theoretical bases / Betty Hanley and Janet Montgomery -- Theory, research, and the improvement of music education / Ian Westbury -- Critical thinking / Betty Ann Younker -- Improvisation / Christopher D. Azzara -- Improvisation and curriculum reform / Edward Sarath -- Adult education / Don D. Coffman -- Music and early childhood education / Joyce Jordan-DeCarbo and Jo Ann Nelson -- Systematic research in studio instruction in music / Richard Kennell -- Distance learning and collaboration in music education / Fred J. Rees -- Looking multiple ways in research / Rosamund Shuter-Dyson -- Learning theories as roots of current musical practice and research / Laurie Taetle and Robert Cutietta -- Systematic instruction / Barak Rosenshine, Hildegard Froehlich and Inshad Fakhouri -- Behavioral research on direct music instruction / Patricia E. Sink -- Self-regulation of musical learning : a social cognitive perspective / Gary E. McPherson and Barry J. Zimmerman -- Motivation and achievement / Martin L. Maehr, Paul R. Pintrich, and Elizabeth A. Linnenbrink -- Developmental characteristics of music learners / Marie Runfola and Keith Swanwick -- Creativity research in music, visual art, theater, and dance / Maud Hickey -- Computer-based technology and music teaching and learning / Peter R. Webster -- Music perception and cognition / Andreas C. Lehmann -- The neurobiology of music cognition and learning / Wilfried Gruhn and Frances Rauscher -- Cognitive constraints on music listening / William Forde Thompson and E. Glenn Schellenberg -- The development of musical abilities / Heiner Gembris -- A comparative review of human ability theory : context, structure, and development / Bruce Torff -- Making music and making sense through music : expressive performance and communication / Reinhard Kopiez -- Taking an acquired skills perspective on music performance / Andreas C. Lehmann and Jane W. Davidson -- Social and cultural contexts of music teaching and learning / Marie McCarthy -- The sociology of education and connections to music education research / Stephen J. Paul and Jeanne H. Ballantine -- Perspectives from the sociology of music / Renate Mueller -- Social psychology and music education / Adrian C. North, David J. Hargreaves, and Mark Tarrant -- Music, culture, curriculum, and instruction / Barbara Reeder Lundquist -- Feminism, feminist research, and gender research in music education : a selective review / Roberta Lamb, Lori-Anne Dolloff, and Sondra Wieland Howe -- The social construction of music teacher identity in undergraduate music education majors / Paul G. Woodford -- Transforming research in music education history / Gordon Cox -- Music transmission and learning : a conspectus of ethnographic research in ethnomusicology and music education / C.K. Szego -- Community music : toward an international overview / Kari Veblen and Bengt Olsson -- Fuzzy teacher education / James Raths -- Reform-minded music teachers : a more comprehensive image of teaching for music teacher education / Dennis Thiessen and Janet R. Barrett -- Teaching as a profession : two variations on a theme / Randall Pembrook and Cheryl Craig -- Changing concepts of teacher education / Glenn E. Nierman, Ken Zeichner, and Nikola Hobbel -- Strengthening the teaching of music educators in higher education / Susan Wilcox and Rena Upitis -- Research by teachers on teacher education / Mary Leglar and Michelle Collay -- Research in music student teaching / Roger Rideout and Allan Feldman -- Professional development / Mary Ross Hookey -- The growing impact of partnerships : a reason for research / Richard J. Deasy -- Policy issues in connecting music education with arts education / David E. Myers and Arthur C. Brooks -- The evaluation of arts partnerships and learning in and through the arts / Hal Abeles ... [and others] -- The use and abuse of arts advocacy and its consequences for music education / Constance Bumgarner Gee -- Research in visual art education : implications for music / Lynn Galbraith -- A review of research in theater, dance, and other preforming arts education : implications for music / Kent Seidel -- Music and neuroscience / John W. Flohr and Donald A. Hodges -- Performing arts medicine / Alice G. Brandfonbrener and Richard J. Lederman -- Musicians' health / Kris Chesky ... [and others] -- Nonmusical outcomes of music education : historical considerations / Michael L. Mark -- Teaching other subjects through music / Merryl Goldberg and Carol Scott-Kassner -- Research : a foundation for arts education advocacy / Liora Bresler -- Scholarly inquiry and the research process / Jack J. Heller and Nicholas DeCarbo -- Maintaining quality in research and reporting / Jack j. Heller and Edward J.P. O'Connor -- Trends in data acquisition and knowledge development / Lee R. Bartel and Rudolf E. Radocy -- Assessment's potential in music education / Richard Colwell -- Contemporary issues in qualitative research and music education / David J. Flinders and Carol P. Richardson
Previous edition has title: Handbook of research on music teaching and learning
Includes bibliographical references and index
Keywords: Music -- Instruction and study